The New Social Movement of Nirkala Bali Community: The Struggle of the Individuals with Sensory Visual Disability Against the Stereotype as Masseuses in Bali - Ni Ketut Ari Kesuma Dewi; I Made Bhasudewa Krisna Narotama Pande (Universitas Udayana, 2024)
This article investigates the movement of sensory visual disability individuals in Denpasar, Bali. The Nirkala Bali Community took the initiative to challenge prevailing stereotypes that link people with sensory visual impairments solely to occupations such as massage therapists and special education teachers. Instead, they underwent a significant transformation and actively participated in the arts sector. This paper aims to determine the success or lack thereof of their movement and to identify any growing support or awareness for it. This study employed a phenomenological approach and recruited participants from the entire Nirkala Bali Community. In-depth interviews and observations of artistic works uploaded to YouTube comprised the data collection process. This article serves as an introduction to the activism of the Nirkala Bali Community, which is representative of the sensory visual disability movement in Bali. This study is expected as the introduction that will facilitate comprehension of their endeavors to combat the pervasive stigmatization that pervades society.